A Strategy to Design Cu2MoS4@MXene Composite With High Photothermal Conversion Efficiency Based on Electron Transfer Regulatory Effect - Li, Lihua; Zhang, Jifan; Lin, Yang; Zhang, Yongfeng; Li, Shujie; Liu, Yanzhen; Zhang, Yingxu; Shi, Leilei; Yuan, Shouzhang; Guo, Lihao (Frontiers in Bioengineering and Biotechnology, 2022)
Using Photothermal therapy to treat cancer has become an effective method and the design of photothermal agents determines their performance. However due to the major radiative recombination of photogenerated electron in photothermal materials, the photothermal performance is weak which hindering their applications. In order to solve this issue, preventing the radiative recombination and accelerating nonradiative recombination, which can generate heat, has been proved as a reasonable way. Herein, we demonstrated a Cu2MoS4@MXene nanocomposite with an obviously enhanced photothermal conversion efficiency (η=87.98%), and this improvement can be attributed to the electron migration. Then, a mechanism is proposed based on the electron transfer regulatory effect and the localized surface plasmon resonance effect, which synergistically promote the nonradiative recombination and generate more heat. Overall, our design strategy shows a way to improve the photothermal performance of Cu2MoS4, and this method can be extended to other photothermal agents to let them be more efficient to treat cancer.